PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN SAMPAH PLASTIK UNTUK EKONOMI LOKAL BERKELANJUTAN DI KABUPATEN TUBAN - Mohamad Ainul Yaqin Romadhoni Mohamad Ali Afandi; Muhammad Anshori (Marsialapari: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity focused on reducing plastic waste problems in Tuban Regency. Plastic waste has long been a concern because its volume keeps increasing and is rarely reused for economic purposes. Through this program, local residents were encouraged to learn how to turn plastic waste into useful and marketable items. The activity involved practical training, direct mentoring, and the formation of small community-based business groups. Islamic values such as trust, responsibility, and cleanliness were introduced throughout the process. After several sessions, residents showed positive changes in environmental awareness and entrepreneurial skills. The program not only helped to lessen plastic waste but also opened new economic opportunities for the community. It is expected that this initiative can become an example of community empowerment based on local potential in Tuban Regency.